ANALISIS RASIO PROFITABILITAS PADA PT. BENAKAT PETROLEUM ENERGY Tbk. - Ardiansyah Ardiansyah; Hamid Halin; Endah Dewi Purnamasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
Ratio Analysis Profitability At PT. Benakat Petroleum Energy Tbk period 2007-2012. Purpose of this study was to determine the profitability of the financial condition of PT. Benakat Petroleum Energy Tbk period 2007-2012. By using the ratio of profitability based on financial ratios will be able to know and evaluate the financial condition of the company. Source of data in this research is secondary data. Secondary data such as financial statements for 2007-2012 were obtained from the Indonesia Stock Exchange that the financial statements for 6 years. This type of research is quantitative data. In this study, quantitative data in the form of data relating to the financial statements. While the data analysis method used is the analysis of profitability ratios. The analytical tool used in this study Return on Assets, Return on Equity, Net Profit Margin, Gross Profit Margin. From the results of analysis show that the company's profitability in the period 2007-2012 PT. Benakat Petroleum Energy Tbk return on assets decreased in 2007 and 2008 although in 2009 increased but in 2010 and 201 declined again until 2012 increased again, while the return on equity decreased only in 2010 and 2011, the net profit margin occurred a substantial decline in 2007 and 2008 although in 2009 increased but in 2010 and 2011 decreased again at the end of 2012 to increase again, and for gross profit margin decrease and increase in each year of the lowest in 2008 and highest in 2012. These results indicate that the performance of the company in managing its finances in terms of profitability ratio and efficient yet stable enough to run the company's day-to-day operations.